Comparative study of high-dose Xuezhikang and low-dose Xuezhikang plus ezetimibe on pro- and anti-inflammatory markers. (February 2013) - Liu, Jun; Luo, Song-Hui; Qing, Ping; Di, Long-Hui; You, Xiang-Dong; Han, Hong-Yan; Jia, Yan-Jun; Li, Xiao-Lin; Wen, Dan; Li, Jian-Jun
Aim: To investigate the effects of two different therapeutic regimes that may obtain equivalent LDL cholesterol (LDL-C) reduction (2400 mg of Xuezhikang [XZK] per day and coadministration of 600 mg of XZK plus 10 mg of ezetimibe [EZT] per day) on plasma levels of inflammatory markers in patients with dyslipidemia.Methods: A total of 46 patients with dyslipidemia were studied and were randomly divided into the two groups: group A (2400 mg XZK per day; n = 23) and group B (600 mg XZK/10 mg EZT per day; n = 23) for 6 weeks. The plasma levels of IL-6, IL-10 and CRP were analyzed at both baseline and 6 weeks.Results: Both therapy regimes resulted in similar reductions of LDL-C (p > 0.05). Compared with baseline, both treatments significantly increased plasma IL-10 and decreased IL-6, as well as CRP levels (p < 0.05 and p < 0.01, respectively), while no difference was found between the two groups (p > 0.05).Conclusion: When achieving a similar reduction in LDL-C, coadministration of low-dose XZK and EZT could also exert anti-inflammatory effects comparable with those obtained by single high-dose XZK.